A new levelling process using skew-arranged roll sets for the doubly-curved plate - Lee, Chang-Whan; Yang, Dong-Yol; Ham, Hyung-Chul; Yoon, Sung-Pil (KOREAN SOC PRECISION ENG, 2016)
In order to flatten the doubly-curved plate both in the longitudinal direction and in the transverse direction, a new levelling process using skew-arranged roll sets was proposed. The effect of the levelling process using skew-arranged roll sets was investigated with finite element analysis. Skew angle of the roll set determines the ratio of the bending moment in the longitudinal direction to the bending moment in the transverse direction. The intermesh of the roll set determines the magnitude of the deformation. Sheets with sheared protrusions, which were bent in both directions, were employed in experiments of the levelling process using skew-arranged roll sets. In the finite element analysis and experiments, bending deformation in both directions was removed at the same time by using the levelling process using two skew-arranged roll sets.
Keywords: CARBONATE FUEL-CELL; PROCESS DESIGN; SHEET; BENT